The Field screening of elite Cacao (Theobroma Cacao L.) clones to vascular streak dieback (VSD) disease as the selection criteria for planting materials: Screening of Cacao Clones for VSD Disease as Selection for Elite Planting Material - Gibson, Entuni; Hollena, Nori; Rebicca, Edward; Ahmad Kamil, Mohd Jaafar (Dr. K. Ashokkumar, PhD., PDF (Canada), 2022)
The field screening for VSD disease infection in four elite cocoa clones (KKM22, KKM4, PBC230, and MCBC1) was conducted after two years of transplanting. This study aimed to determine the efficient selection criteria for planting material of cocoa-based on the intensity of VSD disease and new shoot regeneration characteristics such as number, length, and diameter of new shoots after removal of the infected VSD twigs. Around half population (60%) of the trees were infected by the disease but the infection was minor and observed only on the leaf and twigs of 150 mm in length along the jorquette branches. The MCBC1 clone with a disease severity score of 1.82 is classified under the VSD disease resistance clone whereas other clones with a score averaging 2.21 are grouped under the moderately resistance clone. The cultural practice via pruning of all infected twigs (150 mm) was efficient to control the disease from spreading. One month after pruning, the MCBC1 from disease resistance clone had the lengthiest (62.3 mm) and thickest diameter (15.6 mm) of the new shoot compared with other clones. This study indicates the need for the screening of VSD disease in cocoa plantations so that the disease can be managed and controlled at the early stage of infection. This study also reported the first finding on using new shoot regeneration after pruning for the selection criterion of cocoa planting material in the future breeding programme.